Leymann inventory of psychological terror scale: Development and validation for Portuguese accounting professionals - Rui Silva; Margarida Sim\~oes; Ana Paula Monteiro; António Dias (Economies, 2021)
This research aims to adapt the Leymann Inventory of Psychological Terror and its use on Portuguese Accounting Professionals. Leymann scale was applied in a final sample of 478 accountants aged between 28 and 68, of which 47.5% were men and 52.5% women. We used a quantitative methodology by applying a questionnaire survey whose results were, in the following research phase, analyzed using the statistical packages SPSS 26 and AMOS 27. We used SPSS 26 for the Descriptive Statistical Analysis and AMOS 27 to estimate the structural equation model that validated the scale. After the scale had been adapted and changed, it was validated in psychometric terms to be applied to and used in studies involving this type of professionals. The Accountants Leymann Inventory of Psychological Terror that resulted from adapting the original model was tested using structural equation modelling. Thus, the new scale produced significant results similar to those of the original scale, which means that it is valid and can be applied to other contexts. The validity and statistical reliability of the new scale made it possible to measure mobbing problems among accounting professionals reliably and robustly. The present research is an important contribution to the literature. Although it has been applied in several contexts, it is the first time it is being developed, adapted, and validated for accounting professionals who work in this area of management.
Keywords: 330; accounting professionals; management; mobbing; psychological terror